Mental Health and Academic Stress among University Students: A Review of Risk Factors and Intervention Strategies - Dr. Ravindra Kumar (International Journal of Integrative Studies (IJIS), 2026)
University life is a specific time of life that can be very challenging and formative, as students have to deal with academic challenges while navigating life's developmental, social and financial challenges as well. The present review was conducted to compile the empirical findings pertaining to the model of linking academic stress with the mental health of University students; the sources of literature used were mainly systematic and meta-reviews published between 2015 and 2026, as well as empirical studies. Results have shown a high prevalence of depression (around 41% of the students), anxiety (34-38%), and psychological distress (up to 58%) among students, with significant variation depending on the measurement instruments, disciplines, and world regions [1,3,4]. Stress risk factors encompass academic (increased workload, pressure as shown by exams or competition), psychological (low self-efficacy, perfectionist tendencies), social (family expectations, low social support), financial and lifestyle factors, with sleep disturbances and problematic technology use being especially consistent stress risk factors [2,6,8,10]. The implications reach beyond just personal suffering, to a quantifiable drop in performance in schoolwork, increased drug and alcohol consumption and, in extreme situations, suicidal thoughts [3,9]. Intervention research shows that structured, skills-focused interventions are associated with small-to-moderate decreases in stress, anxiety and depressive symptoms, including digital interventions, which can be an effective addition to in-person interventions [13–20]. Stigma, lack of mental health literacy, and also structural constraints like long waiting times and lack of awareness of mental health services, however, continue to discourage seeking help despite its availability [21–30]. The review concludes that there is a need to move forward, and a layered stepped-care approach (universal prevention, low-intensity broadly accessible interventions and specialist care and institutional policy change) is the most promising way, although there are some methodological limitations in the field, predominance of cross-sectional design and geographical irregularity of evidence, which hamper causal understanding.